Mens Rea and Causal Nexus in Public Procurement Corruption: Reconstructing Anti-Corruption Frameworks in ASEAN - Seroja, Triana Dewi; Chansrakaeo, Ruetaitip; Febriyani, Emiliya; Hutauruk, Rufinus Hotmaulana; Alhakim, Abdurrakhman (Universitas Muhammadiyah Purwokerto, 2026)
Public procurement corruption is one of the most prevalent forms of corruption, with one of the most dangerous and potentially catastrophic impacts on public interests. Despite the continuous efforts to battle corrupt in Indonesia, Malaysia, and Thailand, the three countries are still haunted by the possibility of public procurement corruption, which can significantly stunt their economic growth and overall prosperity. Employing the normative legal research method, this study aims to assess the legal implications of corruption in public procurement and make a case for the acknowledgement of aggravating factors in the relevant criminalization. For this objective, this study analyzes elements of mens rea and causal nexus in the countries’ relevant anti-corruption frameworks. Analysis conclusively reveals that the three countries are not equipped to tie mens rea and causal nexus due to the lack of distinction between them in the relevant frameworks. The study therefore recommends possible amendment by adding a provision that would enable a dual-layered culpability approach, tying mens rea and the actual evidence of corrupt act to the knowledge of possible harm that the perpetrators have, to potentially build a case for a stronger punishment, or provide better normative foundation for future legal developments with the explicit acknowledgement of the broader harms caused by public procurement corruption. The significance of this study lies in its effort to increase the awareness on corruption, particularly by assessing the impacts of public procurement corruption and the mental state behind it, to ultimately make the legal case for harsher punishments against this enduring crime that has stunted growth in Indonesia, Malaysia, and Thailand